Midwifery Care for Over 35 Years Multigravida Mothers with Premature Rupture of Membranes at the Age of a Term Pregnancy - Erica Diana Putri; Finta isti kundarti; Ririn Indriani; Dwi Estuning Rahayu (KHD Production, 2025)
Premature rupture of membranes (PROM) is a condition of rupture of the amniotic membrane after 37 weeks of gestation but before labor begins, which can increase the risk of intraamniotic infection, preterm labor, and operative measures such as cesarean section. This study aims to provide midwifery care for a case of PROM in a multigravida mother aged >35 years with a term pregnancy. This study used a case study design with an in-depth approach to the subject, Mrs. LN, age 40 years, G4P3003, gestational age 37 weeks, who came with complaints of discharge from the birth canal without adequate contractions. Data was collected through interviews, observation, physical examination, and documentation study. Examination using the Leopold palpation method, vaginal toucher, and examination with red litmus paper, which turns purple, indicating the presence of amniotic fluid. The diagnosis was the first stage of the labor latent phase with PROM. Obstetric interventions were carried out through observation, education, and referral to the hospital due to indications for postpartum MOW contraception. The study results showed that the mother and baby were born in good health, and the postpartum contraception plan could be implemented. This study emphasizes the importance of early detection of PROM and collaborative management in supporting maternal and infant safety.